Stratifikasi sosial pada masa prasejarah di Bali - I Wayan Ardika; I Ketut Setiawan; I Wayan Srijaya; Rochtri Agung Bawono (Universitas Udayana, 2017)
Mortuary practices might have represented social stratification during the prehistoric period in Bali. Disposal treatment of the decease, burial goods, and containers that were utilized for burials may correspond with social identity and social persona of the deads and their family. This article will explore social stratification on the basis of burial systems and burial goods that were utilized during the prehistoric period in Bali. Field survey and study on documents have also been done for data collection. In addation, Postprocessual theory has been applied in this study. It seems that global contacts and access for exotic goods might have stimulated the ranked or social stratification during prehistoric period in Bali. Metal objects, which raw materials are absence in Bali, including stone and glass beads, gold foil eye covers that were utilized as burial goods might have represent a status symbol during prehstoric period in Bali. Local elits in Bali utilized material objects as well as burial systems as a symbol for social differentiation and hierarchies in the soceity. Ranked society occurred prior to the apperance of Early State in Bali.